Conservation Status of Agarwood-Producing Species (Gyrinops versteegii) in Indonesia - Sutomo Sutomo; Rajif Iryadi; I Made Sumerta (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Aquilaria malaccensis and Gyrinops versteegii are agarwood producing plant species that is widely used because of its fragrance. Gyrinops versteegii has not been much cultivated and along with the decreasing population of G. versteegii in its natural habitat. This study aimed to assess scarcity status of Gyrinops versteegii based on distribution records from both herbarium and field exploration to assist the formulation of its conservation policy. Distribution data were obtained from online database and also from field exploration in Lombok, Sumbawa, and Flores Islands to obtain the population information. Area of Occupancy (AOO) and Extent of Occurrence (EOO) were calculated using GeoCAT (Geospatial Conservation Assessment Tool) and IUCN status recommendation was discussed. The estimated EOO was 868,422,919 km2, exceeding the value required for the threatened category. Based on EOO, it is included in the Least Concern (LC) category, but the EOO covers a large area of the ocean so the AOO was 116 km2 as meets criterion B (AOO500 km2). It can be categorized into endangered (EN). Population data and conservation status of G verstegii are very important to provide recommendations on the quota wild-harvesting of agarwood by stakeholders.